2017
DOI: 10.1002/vms3.55
|View full text |Cite
|
Sign up to set email alerts
|

Serological survey ofLeptospira interrogans,Toxoplasma gondiiandTrypanosoma cruziin free roaming domestic dogs and cats from a marginated rural area of Yucatan Mexico

Abstract: To evaluate the serological status for Trypanosoma cruzi, Toxoplasma gondii and Leptospira interrogans antibodies in free roaming dogs and cats from a marginated rural community in Yucatan Mexico, 100 households were visited and animals sampled. From the 106 samples, 93 were from dogs and 13 were from cats. Frequency of positive results for T. gondii, T. cruzi and Leptospira spp was 97.8%, 9.7% and 45.2% for dogs and 92.3%, 0.0% and 15.2% for cats, respectively. No associations with age, sex and body condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…In a study conducted in three Mexican cities (Mérida, Umán and Tulum) in Yucatán, 7.8% of 95 cats were positive by ELISA and Western blot, using excreted superoxide dismutase as antigen [122]. Interestingly, no infection was observed in other studies conducted in distinct parts of Mexico [32,38,39].…”
Section: Trypanosoma Cruzi Infection and CD In Catsmentioning
confidence: 94%
See 1 more Smart Citation
“…In a study conducted in three Mexican cities (Mérida, Umán and Tulum) in Yucatán, 7.8% of 95 cats were positive by ELISA and Western blot, using excreted superoxide dismutase as antigen [122]. Interestingly, no infection was observed in other studies conducted in distinct parts of Mexico [32,38,39].…”
Section: Trypanosoma Cruzi Infection and CD In Catsmentioning
confidence: 94%
“…In Mexico, a study conducted in 2010 reported a prevalence of 34% [31], while another study carried out in 2017 detected a prevalence of 4.4% [32]. Other studies conducted in Mexico have reported different prevalence values [33][34][35][36][37][38][39][40][41][42][43]. Recently, anti-T. cruzi antibodies were detected in 50% (17/34) of dogs from two rural settlements in the Sierra de Los Tuxtlas, Veracruz, Mexico [44].…”
Section: Trypanosoma Cruzi Infection and CD In Dogsmentioning
confidence: 99%
“…Serologic diagnosis of Leptospira spp. : Antibodies were approached using the microscopic agglutination test (MAT) [ 11 ]. MAT is considered the gold standard of reference for the diagnosis of leptospirosis and was performed using live antigens at the laboratory of the Faculty of Medicine of the Autonomous University of Yucatan under the World Health Organization’s protocols.…”
Section: Case Presentationmentioning
confidence: 99%
“…During the rainy season, water is not easily absorbed by the rough soil, generating puddles where animals find drinking sources. Leptospirosis prevalence in humans in the region was reported to amount to 14.1% in 1984 and 14.2% in 2002; it was more prevalent in rural areas than in urban ones, with 74.3% of the reported cases occurring during the rainy season [ 11 ]. In a seroprevalence study conducted on humans in 2018 in the same area, seropositivity of 35% was reported [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…En la búsqueda de mejores y más rápidas pruebas diagnósticas para la leptospirosis, se diseñó una prueba de diagnóstico rápida y confiable de ELISA la cual ofrece un pronto diagnóstico para zonas remotas con escaso acceso a laboratorios especializados (Abdoel et al, 2011). Estudios epidemiológicos más recientes en zonas rurales de alta marginación de Yucatán revelan seroprevalencias de 45.2 % y 15.2 % en perros y gatos, respectivamente, incluyendo los serovares Canicola, Autralis y Bratislava fueron las de mayor circulación (Ortega-Pacheco et al, 2017). Un posterior estudio epidemiológico en gatos de la ciudad de Mérida, Yucatán, demostró una seroprevalencia del 17% en los cuales la serovariedad Australis fue la más predominante (54.3 %) seguida de la Pyrogenes (15.3 %) y Gryppotyphosa (13.0 %) (Ortega-Pacheco et al, 2020).…”
Section: Introductionunclassified